INTEGRASI WORDWALL DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN LITERASI SISWA KELAS KELAS III DI SDN GUNGGUNG 1 - Ummul Khalifah; Ari Nur Iqbal; Shofiatul Fajria Wandi; Ranah Minang Chaniago (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this study is to find out how the implementation of Wordwall-based learning media can improve scientific literacy and student interest in learning science at SDN GUNGGUNG 1. This study uses a qualitative research method with data collection techniques through observation, interviews, and documentation. The research was conducted at SDN Gunggung I. Interviews were conducted on October 5, 2025, and observations were carried out on December 7, 2025. The research subjects were third-grade students of SDN Gunggung I, while the third-grade teacher acted as an informant to support data collection during observations and interviews. The results of this study indicate that the use or implementation of Wordwall learning media in third-grade science lessons at SDN Gunggung I can improve students' scientific literacy and interest in learning.